The effect of soybean-to-water ratio level of coagulant, and soaking time on the sensory qualities of taho - Yu, Lilian S.; Arcellana Mayi Y. (1978.)
This research was designed to give a laboratory-scale procedure for taho which would ensure constancy of the quality characteristics of the product. In order to do so, three critical factors involved in the process of making taho were singled out, the factors being: soybean-to-water ratio, level of coagulant, and soaking time of soybeans. In phase I, combinations of the first two variables were subjected to sensory evaluation and the sensory data subjected to statistical analyses in order to ascertain the best combination. Soybean-to-water ratios of 1:3, 1:4, and 1:5 were coupled with coagulant levels of 1/2 tsp., 3/4 tsp., and 1 tsp. The most satisfactory combination was found to be 1:5 soybean-to-water ratio at a coagulant level of 1 tsp. In phase III, the 1:5 soybean-to-water ratio, 1 tsp. coagulant level combination was coupled with varying soaking times of 4, 5, and 6 hours and the products subjected again to sensory evaluation and the sensory data subjected to statistical analyses in order to ascertain the best combination. The most satisfactory combination was found to be 1:5 soybean-to-water ratio, 1 tsp. coagulant level, 5 hours soaking. Correlation computations indicated significant negative correlation between curb pH ans appearance of the product, while appearance, consistency, and flavor of taho were found to have significant positive correlation with the general acceptability of the product.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Cookery (Tofu); Taho